1998
DOI: 10.1007/s001340050764
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pulmonary mechanics after fiberoptic bronchoalveolar lavage in mechanically ventilated patients

Abstract: BAL in mechanically ventilated patients is associated with deterioration of pulmonary mechanics and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 25 publications
1
25
1
2
Order By: Relevance
“…This may result in transient hypoventilation and derecruitment of alveolar space, especially when the peak ventilation pressure is exceeded and the respiratory cycle has to be aborted. In addition, Klein and coworkers described a deterioration in pulmonary compliance after fiberoptic BAL that may further impair gas exchange [26]. It is therefore necessary to repeat our study with blind methods to find out whether differences in arterial oxygenation between high and low BAL volumes have been obscured by the effects of a bronchoscopic procedure in our study.…”
Section: Discussionmentioning
confidence: 93%
“…This may result in transient hypoventilation and derecruitment of alveolar space, especially when the peak ventilation pressure is exceeded and the respiratory cycle has to be aborted. In addition, Klein and coworkers described a deterioration in pulmonary compliance after fiberoptic BAL that may further impair gas exchange [26]. It is therefore necessary to repeat our study with blind methods to find out whether differences in arterial oxygenation between high and low BAL volumes have been obscured by the effects of a bronchoscopic procedure in our study.…”
Section: Discussionmentioning
confidence: 93%
“…Flexible fibreoptic bronchoscopy is an effective technique for bronchial toilet and diagnosis when ventilator-associated pneumonia is suspected, particularly in cases of ARDS. However, the insertion of a flexible bronchoscope into the tracheal tube of a patient with severe ARDS may have life-threatening consequences, such as pneumothorax [5] or hypoxaemia [12,13]. Indeed, the level of risk may tip the balance between benefit and harm, and this procedure is sometimes avoided in severely ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a specific study with a specific subgroup of patients with ARDS, a more than 30% drop in PaO 2 was observed in 35% of patients 271. A more detailed physiological study in 18 patients undergoing bronchoscopy and BAL has demonstrated adverse change in lung compliance and resistance 267. Post-bronchoscopy pneumothorax has been reported in ventilated patients in whom transbronchial biopsy was not undertaken 246 264…”
Section: Bronchoscopy In the Icumentioning
confidence: 99%